Implementation of ChatGPT on English Class Essay Writing Skills in University Students - Wahyuddin; Hasman Hasman; Andini Ramadhani Idris (Hasanuddin University, 2023)
ChatGPT was widely discussed in the news when it first appeared. In several aspects, this technology is considered to have a large negative impact and has the potential to minimize human narrative abilities. The positive impact that leads to collaboration between human thought and technology, especially in the case of ChatGPT, is that humans and technology can collaborate and create more innovative impacts. This research was created to answer the need for technological developments by using Artificial Intelligence in learning, especially essay writing skills for students through the application of ChatGPT. The subjects of this research were 13 fourth semester students of the English Language Education Study Program at Muhammadiyah University of Parepare. The researcher used quantitative descriptive methods to compare the students' results before and after the essay writing learning treatment by giving a pre-test and post-test. After being given treatment, students' achievement in writing increased during the post-test. It is 2 students (15%) were in the excellent category, 11 students (85%) were classified as good, then none of them were classified as fair, and poor also has zero. This shows that their attention to improving their writing has occurred. The research concluded that the application of ChatGPT to essay writing skills in English classes for higher students is applicable and brings significant benefits.